Gender and linguistic diversity in Romance languages: Traditional phenomena revisited - Zunino, Gabriela Mariel; Tomé Cornejo, Carmela (Borealis – An International Journal of Hispanic Linguistics, 2025)
Bilingual (English-Spanish) introduction to the monographic issue.